Composição química e energética de alimentos para frangos de corte - Troni, Allan Reis [UNESP]; Gomes, Paulo Cezar; De Carvalho Mello, Heloísa Helena; Teixeira Albino, Luiz Fernando; Da Rocha, Tatiana Cristina (My University, 2016)
The aim of this work was to determine the chemical composition and values for apparent metabolisable energy (AME), and apparent metabolizable energy corrected for nitrogen (AMEn), in broiler feeds. In the experiment, 432 male broiler chicks, 14 to 24 days old were used, distributed in a completely randomised design with 12 treatments (11 feeds and a reference diet), six replications and six birds per experimental unit. The method employed was the total collection of excreta. The feeds under study were: Two of viscera meal (VM), two feather and blood meal (FBM), two meat and bone meal (MBM), roasted whole soybean (RWS), soybean meal (SM), ground corn (GC), wheat bran (WB) and millet (M). The values for crude protein and ether extract (%), AME and AMEn (kcal/kg) were respectively: 58.84, 12.64, 3705 and 3340 for VM1; 57.64, 11.66, 3565 and 3241 for VM 2; 80.58, 6.79, 3070 2740 for FBM 1; 82.27, 6.38, 3060 2703 for FBM 2; 48.06, 9.60, 1574 and 1283 for MBM 1; 41.21, 9.08, 1353 and 1088 for MBM 2; 36.45, 20.78, 3192 and 2989 for RWS; 46.22, 1.72, 2648 and 2336 for SM; 8.51, 3.61, 3354 and 3265 for GC; 17.11, 3.14, 1948 and 1788 and for WB; and 12.01, 4.09, 3072 and 2948 for M. The differences found in chemical and energy composition highlight the need for research to revise the nutritional values of feed.
Chemical and energy composition of broiler feeds
Keywords: Alternative feed; Apparent metabolisable energy; Feed of animal origin; Nutrition; Poultry; Soybean